2001
DOI: 10.1046/j.1365-313x.2001.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐dependent salicylic acid regulates an expanded cell death response to a plant pathogen

Abstract: SummaryThe molecular events associated with susceptible plant responses to disease-causing organisms are not well understood. We have previously shown that ethylene-insensitive tomato plants infected with Xanthomonas campestris pv. vesicatoria have greatly reduced disease symptoms relative to wild-type cultivars. Here we show that salicylic acid (SA) is also an important component of the susceptible disease response. SA accumulates in infected wild-type tissues and is correlated with necrosis but does not accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
110
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 42 publications
6
110
1
1
Order By: Relevance
“…However, the reduced accumulation of SA and JA and the suppressed expression of SA-and JAresponsive genes in GH3-8-overexpressing plants strongly suggest that GH3-8-mediated Xoo resistance does not require the activation of SA and JA signaling. This result is consistent with a previous report that showed that the basal resistance for bacterial pathogens in tomato (Solanum lycopersicum) is SAindependent (O'Donnell et al, 2001). However, suppressing auxin signaling by the activation of GH3-8 repressed JA and SA signaling ( Figure 5).…”
Section: Gh3-8 Mediates a Basal Resistance That Does Not Require The supporting
confidence: 94%
“…However, the reduced accumulation of SA and JA and the suppressed expression of SA-and JAresponsive genes in GH3-8-overexpressing plants strongly suggest that GH3-8-mediated Xoo resistance does not require the activation of SA and JA signaling. This result is consistent with a previous report that showed that the basal resistance for bacterial pathogens in tomato (Solanum lycopersicum) is SAindependent (O'Donnell et al, 2001). However, suppressing auxin signaling by the activation of GH3-8 repressed JA and SA signaling ( Figure 5).…”
Section: Gh3-8 Mediates a Basal Resistance That Does Not Require The supporting
confidence: 94%
“…Incompatible interactions have been extensively studied principally because of their direct and practical applications in the field (Vlot et al, 2009), whereas much less 55 consideration has been paid to the compatible interactions (O'Donnell et al, 2001;Huang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired ethylene biosynthesis and responsiveness can lead to altered cell expansion, cell elongation, senescence, abscission, cell death, fruit ripening, root hair formation, lateral root development, nodulation, and sex determination (Bleecker et al, 1988;Guzmán and Ecker, 1990;Oeller et al, 1991;Lanahan et al, 1994;Tanimoto et al, 1995;Wilkinson et al, 1997;O'Donnell et al, 2001;Xu et al, 2006;Boualem et al, 2008;Penmetsa et al, 2008;Hattori et al, 2009;Wang et al, 2010;Lewis et al, 2011). A framework of the ethylene signaling pathway has been assembled using a combination of genetic and biochemical analyses in Arabidopsis (Arabidopsis thaliana; Kendrick and Chang, 2008;Stepanova and Alonso, 2009;Zhao and Guo, 2011).…”
mentioning
confidence: 99%